Research progress in tourism, leisure and hospitality in Europe (1969–2018). Issue 1 (7th December 2020) - Mulet-Forteza, Carles; Lunn, Erika; Merigó, José M.; Horrach, Patricia
Abstract : Purpose: This study aims to present a bibliometric overview of articles published in the field of tourism, leisure and hospitality and analyzed by researchers mainly affiliated with European institutions. Design/methodology/approach: The authors conducted a bibliometric study of journals included in the Web of Science related to the field of tourism, leisure and hospitality in 2019. The review incorporates various techniques to determine the field's structure from a scientific and intellectual perspective. Findings: The results are valuable for several reasons. First, they will support researchers in identifying those topics with the greatest potential for advancing research in this field. Second, they will constitute an important aid in the design of new policies for journal publishers. Practical implications: This study can lead to advances in the tourism, leisure and hospitality field, as it identifies the publication trends of researchers who are mainly affiliated with European institutions. It also offers useful information for practitioners and academics in their endeavor to identify gaps in the extant literature and future trends. Originality/value: No other studies have analyzed this field for a period of this length.